Rural development: role of state - Wghmore, Suryakant (2002)
How successful have government interventions been in fostering rural development by encouraging people's participating and NGO activity? A first step in sustained rural development lies in ending the historical deprivation of ccommunities and peoples long marginalised. - Reproduced.
Keywords: Rural development